Paternal age affects offspring via an epigenetic mechanism involving REST/NRSF. (5th January 2021) - Yoshizaki, Kaichi; Kimura, Ryuichi; Kobayashi, Hisato; Oki, Shinya; Kikkawa, Takako; Mai, Lingling; Koike, Kohei; Mochizuki, Kentaro; Inada, Hitoshi; Matsui, Yasuhisa; Kono, Tomohiro; Osumi, Noriko
Abstract: Advanced paternal age can have deleterious effects on various traits in the next generation. Here, we establish a paternal‐aging model in mice to understand the molecular mechanisms of transgenerational epigenetics. Whole‐genome target DNA methylome analyses of sperm from aged mice reveal more hypo‐methylated genomic regions enriched in REST/NRSF binding motifs. Gene set enrichment analyses also reveal the upregulation of REST/NRSF target genes in the forebrain of embryos from aged fathers. Offspring derived from young mice administrated with a DNA de‐methylation drug phenocopy the abnormal vocal communication of pups derived from aged fathers. In conclusion, hypo‐methylation of sperm DNA can be a key molecular feature modulating neurodevelopmental programs in offspring by causing fluctuations in the expression of REST/NRSF target genes. SYNOPSIS: Paternal aging affects health and disease of the next generation, but the causative mechanisms are largely unknown. This study identifies hypo‐methylated sites enriched in REST/NRSF motifs in sperm DNA as epigenetic key features for inheritance. Paternal aging induces vocal communication deficits in pups at the infant stage. Sperm DNA from aged mice contains 96 hypo‐methylated regions enriched in REST/NRSF motives. REST signature genes are upregulated in the embryonic brain of the offspring of aged fathers. Offspring of young mice treated with a DNA de‐methylating drug phenocopy vocal communication deficits. Abstract : Paternal aging affects health and disease of the next generation, but the causative mechanisms are largely unknown. This study identifies hypo‐methylated sites enriched in REST/NRSF motifs in sperm DNA as epigenetic key features for inheritance.